Is Differentiated Instructional Strategy Worth to Try in Physics Lessons for High School Students? A Literature Review - Nugroho, Drajat Agung; Musliman, Acep (MJI Publisher, 2024)
This study investigates the feasibility and effectiveness of differentiated instructional strategies in high school physics education through a systematic literature review. The analysis encompasses 10 recent studies (2019–2024) that explore various implementations of differentiated learning in physics lessons. Results indicate that differentiated instruction enhances academic performance, critical thinking, and problem-solving skills by tailoring lessons to diverse student needs, including multiple intelligences and learning styles. Additionally, differentiated strategies facilitate student-centered learning and foster engagement, addressing the challenges of traditional teaching methods. However, resource intensity and technological gaps present significant barriers to implementation. Findings suggest that professional development and adaptive technologies are essential to supporting teachers in overcoming these challenges. This review underscores the transformative potential of differentiated instruction to democratize learning and meet the varied needs of modern classrooms, particularly in the context of post-pandemic educational recovery. The study concludes with recommendations for integrating differentiated instructional strategies into high school physics curricula to optimize both short-term and long-term educational outcomes.